Audit Pengkodean Klinis Menggunakan Aturan Morbiditas di Rawat Inap Rumah Sakit Umum Daerah Sultan Suriansyah Banjarmasin - Ayu Dwi Anissa; Nina Rahmadiliyani; Khairunnisa Khairunnisa (Jurnal Kesehatan Indonesia, 2026)
Clinical coding audits are necessary to review and analyze identified errors and to trace their sources by comparing the information produced by clinical coders with the data documented in patients’ medical records. Sultan Suriansyah Regional General Hospital Banjarmasin has never conducted a clinical coding audit. This study aimed to evaluate clinical coding audits using morbidity rules in inpatient medical records. This study employed a mixed-method approach with a quantitative design supported by qualitative data. A total of 99 inpatient medical record files were reviewed. The main informant was the inpatient coding officer, while triangulation informants included the inpatient BPJS doctor/verifier and the head of the medical records unit. Data were collected through observation and interviews using observation and interview guidelines, and analyzed using univariate analysis. The results of the study showed that, based on morbidity rules, the reliability of diagnosis coding was 91% consistent (90 medical records) and 9% inconsistent (9 medical records), mainly due to preliminary diagnoses that required supporting examinations to establish final diagnoses. Diagnosis completeness reached 100% (99 medical records), as completeness has been established as a standard. Coding accuracy was 93% accurate (92 medical records) and 7% inaccurate (7 medical records), primarily due to differences in ICD-10 code selection. Relevance of coding was 96% appropriate (95 medical records) and 4% inappropriate (4 medical records), which was influenced by the high workload of coding officers, leading to coding errors. In conclusion, clinical coding audits using morbidity rules at Sultan Suriansyah Regional General Hospital Banjarmasin revealed that several audit elements, particularly reliability, accuracy, and relevance, have not yet achieved optimal results.